Eksistensi Program Siaran Jaga Malam di RRI 92,4 Mhz Pro 2 Medan Pada Kalangan Remaja - Sinaga, Stella; Sahputra , Dedi; Khairulla , Khairulla (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study examines the existence of the Jaga Malam broadcast program on RRI 92.4 MHz Pro 2 Medan among adolescents. In the midst of stiff competition with digital platforms such as Spotify and Joox, the program has managed to maintain its popularity through innovative strategies. The research method uses a descriptive qualitative approach with a purposive sampling technique involving 10 informants consisting of the Head of the Broadcasting Division, broadcasters, and adolescent listeners. Data collection was carried out through participatory observation, structured interviews, and documentation. The results of the study show that the existence of the Jaga Malam program is supported by five main factors: the selection of content relevant to adolescent life, the casual and interactive broadcasting style, the use of digital platforms through RRI PLAY GO and the rri.co.id website, active interaction through social media, and the development of the "Temen Pro 2" listening community. This program not only functions as entertainment but also has a positive impact as a forum for self-expression, a source of inspiration, a companion at night, and an informal educational facility for adolescent listeners.